Can cooperative business models solve horizontal and vertical coordination challenges? A case study in the Australian pineapple industry. Issue 2 (December 2022) - Rolfe, John; Akbar, Delwar; Rahman, Azad; Rajapaksa, Darshana
Abstract: For agricultural products, cooperative systems are an alternative to independent business arrangements that can be used to solve the simultaneous need to coordinate supply from disaggregated producers and improve efficiencies. This study analyses how a hybrid cooperative business model can solve horizontal and vertical coordination challenges, drawing on an analysis of a pineapple cooperative business, Tropical Pines, in Queensland. Semi-structured interviews with a cross section of key stakeholders and thematic content analysis are used to identify key factors. Leadership, information sharing, trust, market forecasting, risk sharing, accountability, and provision of agronomic and other support to growers are identified as key factors that distinguish this cooperative hybrid model from more standard business models. Achieving both horizontal and vertical integration maximises resource utilisation and returns to growers, as well as reducing market uncertainty and maximizing product consistency. However, there are also higher costs involved with hybrid models, particularly the focus on communication and engagement required to maintain the trust of growers. These costs increase with the size and complexity of the cooperative, which creates a tension because size and scale are often required to generate the efficiencies and market power necessary to deliver benefits. Highlights: Cooperatives can coordinate agricultural supply chains in horizontal and vertical dimensions. This study analyses a pineapple cooperative business in Australia. Achieving simultaneous horizontal and vertical integration maximises resource utilisation. Higher costs mean cooperative models need to deliver higher returns.